DESCRIPTION ON THE PATIENTS’ CHARACTERISTICS OF ABNORMAL UTERINEBLEEDING BASED ON STRUCTURAL AND NON-STRUCTURAL ETIOLOGY - Silvia Maya Ananta; Jimmy Yanuar Annas; Lilik Herawati (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2021)
Abnormal uterine bleeding (AUB) is a problem frequently experienced by women in the world. AUB is not a disease but a symptom that indicates a problem in the female reproductive system or organs. The purpose of research was to determine the description of the patients’ caracteristics of AUB with structural (PALM) and non-structural (COEIN) etiologies. This analytical description study used medical record data from AUB patient in Dr. Soetomo District General Hospital Surabaya in January-December 2019. The number of samples of this study was 65 data, with 36 data for structural etiologies (PALM) and 29 data for non-structural etiologies (COEIN). Caracteristic of patient were seen from 3 categories, i.e., age, parity status, and body mass index (BMI) from 2 etiological categorie